2010
DOI: 10.1029/2010gl044007
|View full text |Cite
|
Sign up to set email alerts
|

Increasing intensity of El Niño in the central‐equatorial Pacific

Abstract: [1] Satellite observations suggest that the intensity of El Niño events in the central equatorial Pacific (CP) has almost doubled in the past three decades, with the strongest warming occurring in 2009-10. This is related to the increasing intensity as well as occurrence frequency of the so-called CP El Niño events since the 1990s. While sea surface temperature (SST) in the CP region during El Niño years has been increasing, those during neutral and La Niña years have not. Therefore, the well-documented warmin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
518
5
9

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 621 publications
(581 citation statements)
references
References 21 publications
33
518
5
9
Order By: Relevance
“…Further, Yu et al (2016) found that a decreasing trend in the frequency of thunderstorms over China is due to a decrease in moisture transported over the region resulting from decreasing monsoonal rainfall. Similarly, a reduction in Thn activity over India can be attributed to the decline of rainfall activity, and also to a reduction in the amount moisture due to a fall in the frequency of monsoon depressions, and the increasing intensity and trends of ENSO, PDO and AMO warm phases (Dash et al, 2004;Lee and McPhaden, 2010;Kulkarni et al, 2013;Krishnamurthy and Krishnamurthy, 2014a, b). Another possible potential source of reduced thunderstorm activity over India needs to be further explored.…”
Section: Methodsmentioning
confidence: 99%
“…Further, Yu et al (2016) found that a decreasing trend in the frequency of thunderstorms over China is due to a decrease in moisture transported over the region resulting from decreasing monsoonal rainfall. Similarly, a reduction in Thn activity over India can be attributed to the decline of rainfall activity, and also to a reduction in the amount moisture due to a fall in the frequency of monsoon depressions, and the increasing intensity and trends of ENSO, PDO and AMO warm phases (Dash et al, 2004;Lee and McPhaden, 2010;Kulkarni et al, 2013;Krishnamurthy and Krishnamurthy, 2014a, b). Another possible potential source of reduced thunderstorm activity over India needs to be further explored.…”
Section: Methodsmentioning
confidence: 99%
“…The CP ENSO has occurred more frequently in the past few decades (Ashok et al 2007;Kao and Yu 2009;Kug et al 2009). The intensity of El Niño in the central Pacific region, for example, has doubled in the past three decades (Lee and McPhaden 2010), and the El Niño events in the twenty-first century so far have been mostly of the CP type (Yu et al 2012b). Therefore, the effects of ENSO on the WPSH variability need to be considered separately for the two types.…”
Section: Introductionmentioning
confidence: 99%
“…The variability in the annual onset of transition to a reproductive state and subsequent changes to the vocal-acoustic system, including the auditory inner ear and vocal motor system, suggests an equally variable external circannual trigger. The occurrence of El Niño conditions during the winter season of 2010 (Lee and McPhaden, 2010) suggests warming ocean water temperatures may have affected the midshipman breeding population, as has been demonstrated in other fish stocks (Stenseth et al, 2002). Animals may begin the transition from non-reproductive to reproductive state and invest in gonadal development based on internal somatic cues such as nutritional state (Carrillo et al, 2009), which could vary year to year based on food availability due to environmental changes such as water temperature.…”
Section: Timing Of Annual Reproductive Rhythmsmentioning
confidence: 99%